Inflammation and atrial remodeling after a mountain marathon. Issue 3 (18th December 2012) - Wilhelm, M.; Zueger, T.; De Marchi, S.; Rimoldi, S. F.; Brugger, N.; Steiner, R.; Stettler, C.; Nuoffer, J.‐M.; Seiler, C.; Ith, M.
<x xml:space="preserve">Abstract</x> Endurance athletes have an increased risk of atrial fibrillation. We performed a longitudinal study on elite runners of the 2010 Jungfrau Marathon, a Swiss mountain marathon, to determine acute effects of long‐distance running on the atrial myocardium. Ten healthy male athletes were included and examined 9 to 1 week prior to the race, immediately after, and 1, 5, and 8 days after the race. Mean age was 34.9 ± 4.2 years, and maximum oxygen consumption was 66.8 ± 5.8 mL/kg*min. Mean race time was 243.9 ± 17.7 min. Electrocardiographic‐determined signal‐averaged P‐wave duration (SAPWD) increased significantly after the race and returned to baseline levels during follow‐up (128.7 ± 10.9 vs. 137.6 ± 9.8 vs. 131.5 ± 8.6 ms; P < 0.001). Left and right atrial volumes showed no significant differences over time, and there were no correlations of atrial volumes and SAPWD. Prolongation of the SAPWD was accompanied by a transient increase in levels of high‐sensitivity C‐reactive protein, proinflammatory cytokines, total leucocytes, neutrophil granulocytes, pro atrial natriuretic peptide and high‐sensitivity troponin. In conclusion, marathon running was associated with a transient conduction delay in the atria, acute inflammation and increased atrial wall tension. This may reflect exercise‐induced atrial myocardial edema and may contribute to atrial remodeling over time, generating a substrate for atrial arrhythmias.